Nanocomposite Based on Bacterial Cellulose and Silver Nanoparticles Improve Wound Healing Without Exhibiting Toxic Effect - Ozelin, Saulo Duarte; Esperandim, Tábata Rodrigues; Dias, Fernanda Gosuen Gonçalves; Pereira, Lucas de Freitas; Garcia, Cristiane Buzatto; de Souza, Thiago Olímpio; Magalhães, Larissa Fernandes; Barud, Hernane da Silva; Sábio, Rafael Miguel [UNESP]; Tavares, Denise Crispim (Elsevier, 2024)
Wound healing is an important and complex process, containing a multifaceted process governed by sequential yet overlapping phases. Certain treatments can optimize local physiological conditions and improve wound healing. Silver nanoparticles (AgNP) are widely known for their antimicrobial activity. On the other hand, bacterial cellulose (BC) films have been used as a dressing that temporarily substitutes the skin, offering many advantages in optimizing wound healing, in addition to being highly biocompatible. Considering the promising activities of AgNP and BC films, the present study aimed to evaluate the wound healing activity in Wistar Hannover rats using a nanocomposite based on bacterial cellulose containing AgNP (AgBC). In a period of 21 days, its influence on the wound area, microbial growth, histopathological parameters, and collagen content were analyzed. In addition, toxicity indicators were assessed, such as weight gain, water consumption, and creatinine and alanine transaminase levels. After 14 days of injury, the animals treated with AgBC showed a significant increase in wound contraction. The treatment with AgBC significantly reduced the number of microbial colonies compared to other treatments in the first 48 h after the injury. At the end of the 21 experimental days, an average wound contraction rate greater than 97 % in relation to the initial area was observed, in addition to a significant increase in the amount of collagen fibers at the edge of the wounds, lower scores of necrosis, angiogenesis and inflammation, associated with no systemic toxicity. Therefore, it is concluded that the combination of preexisting products to form a new nanocomposite based on BC and AgNP amplified the biological activity of these products, increasing the effectiveness of wound healing and minimizing possible toxic effects of silver.
Keywords: Antimicrobial activity; Bacterial cellulose; Silver nanoparticles; Toxicological assay; Wound healing assay